The Role of Colchicine in Acute Coronary Syndrome - Liemena Harold Adrian; Budi Satrijo; Djanggan Sargowo; Indra Prasetya (Heart Science Journal, 2020)
Background: Despite the advances of current optimal treatment of atherosclerotic disease, the incidence of events after acute coronary syndrome (ACS) remains high. Colchicine, with its well-established pleiotropic anti-inflam- matory effects, may inhibit NLRP3 inflammasome, a key mediator in atherosclerosis-associated inflammation (AAI) thus reducing systemic inflammation. NRLP3 inflammasome activation inside leukocytes (mainly monocytes and neutrophils) is precipitated by cholesterol crystals that are present in all atherosclerosis stages. ???????????????????????????????????????? ???????????????????????????????????????? ???????? ???????????????????????????????????????????????????????????????? ???????????????????????????????????? ???????????????? ???????? ???????????????????????????????????????????????????????? ???????????? ???????????????????????????????????????????????????????? ???????????????? ???????????????????????????? ???????????????????? cytokines are the crucial inflammatory pathway mediators that promote the formation of plaque and instability in the inflammatory cascade.Objective: This review will elaborate on the function of immune cells in atherosclerosis, explain the mechanisms of NLRP3 inflammasome activation in the context of AAI, and address the possible role of colchicine specifically targeting NLRP3 inflammasome and its concomitant downstream mediators in ACS, and provide an overview of current or ongoing studies produced in this area.Discussion : NRLP3 inflammasome activation inside leukocytes (mainly monocytes and neutrophils) is precipitat- ed by cholesterol crystals that are present in all atherosclerosis stages. Subsequent activation of pro-inflammatory ???????????????????????????????????? ???????????????? ???????? ???????????????????????????????????????????????????????? ???????????? ???????????????????????????????????????????????????????? ???????????????? ???????????????????????????? ???????????????????? ???????????????????????????????????? ???????????? ???????????? ???????????????????????????? ???????????????????????????????????????????????? pathway mediators that promote the formation of plaque and instability in the inflammatory cascade. A potential advantage of a medication acting through an inflammatory milieu found in atherosclerotic lesions has recently become the need for novel therapeutic options. Colchicine, with its well-established pleiotropic anti-inflammato- ry effects, may inhibit NLRP3 inflammasome, a key mediator in atherosclerosis-associated inflammation (AAI) thus reducing systemic inflammation.Conclusion: Colchicine is a safe and reliable medication for ACS patients, alongside reveal various benefit in reducing inflammation through inhibition of NLRP3 Inflammasome`